Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1038/hr.2010.186
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of valsartan and amlodipine on cardiorenal protection in Japanese hypertensive patients: the Valsartan Amlodipine Randomized Trial

Abstract: on behalf of the VART InvestigatorsThe Valsartan Amlodipine Randomized Trial, a multicenter, prospective, randomized, open-labeled, blinded-end point trial, was designed to compare the beneficial effects of the angiotensin II receptor blocker valsartan and the calcium channel blocker amlodipine on cardiovascular events in Japanese essential hypertensive patients. The primary end point was a composite of all-cause death, sudden death, cerebrovascular death, cardiac events, vascular events and renal events. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…However, in the valsartan group, significant improvements in left ventricular hypertrophy (LVH) and microalbuminuria were observed. 7 It has been shown that home BP (HBP) is superior to office BP in the prediction of HT-related cardiovascular complications. [8][9][10][11][12] Especially, high morning HBP is closely correlated with organ damage and future cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the valsartan group, significant improvements in left ventricular hypertrophy (LVH) and microalbuminuria were observed. 7 It has been shown that home BP (HBP) is superior to office BP in the prediction of HT-related cardiovascular complications. [8][9][10][11][12] Especially, high morning HBP is closely correlated with organ damage and future cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…In the Valsartan Amlodipine Randomized Trial (VART), 7 we compared the beneficial effects of ARB valsartan and calcium channel blocker amlodipine on cardiovascular events in Japanese patients with mild-to-moderate hypertension. Office BP levels were well controlled and remained similar in the valsartan group and the amlodipine group.…”
Section: Introductionmentioning
confidence: 99%
“…Achieved BP level in the CASE-J Ex was lower than values achieved in other clinical trials directly comparing the effect of ARB with that of amlodipine on the incidence of CV morbidity and mortality in hypertensive patients. 3,13,14 No significant difference was noted between the two groups in the incidence of the primary CV events, all-cause death, or CV death under strict BP control in the CASE-J Ex.…”
Section: Discussionmentioning
confidence: 99%
“…Because the VART patient population is relatively low risk when compared with those of previous trials, statistically evaluating the hard end points is insufficient to confirm the initial hypothesis. 7 However, the researchers showed a significant reduction in the H/M ratio using 123I-MIBG imaging. Advanced healthcare systems that enable patients to visit hospitals often and that widely distribute expensive medical devices (for example, MRI) enable researchers to track the performance of these treatments with highly accurate evaluations in large trials.…”
Section: Conventional Randomized Controlled Trials Versus Probe Testsmentioning
confidence: 98%
“…In this issue, the Valsartan Amlodipine Randomized Trial (VART) study is also added to this list. 7 One of the important features of these large clinical trials held in Japan is that they achieve the same level of BP control from the beginning to the end of the trial (except CASE-J). A direct comparison between CCBs and ARBs carried out in the CASE-J and VART studies revealed no significant difference in the primary end point, but overall cardiac mortality and morbidity are lower in Japan than in other countries.…”
Section: Difficulty Of Large Clinical Trialsmentioning
confidence: 99%